“Nichigetsu-sama” [Soliluna], un cuento de Ango Sakaguchi - Chiappe Ippolito, Matías (El Colegio de México, 2020)
“Nichigetsu-sama”, by Japanese writer Sakaguchi Ango (1906-1955), was published in 1949 and tells the story of Ōji Kimigorō, a young black marketeer who is a friend of the narrator, a writer recently discharged from a mental institution. In the story, they both meet in a bar on one of Tokyo’s darkest alleys to share a night of bizarre encounters and disturbing tales.